The Gymnasium at Home (1861-1912): From a Fashion to a Healthy Lifestyle? - Torrebadella Flix, Xavier (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2020)
When the first hygienic gymnasiums appeared in Spain, in the 1860s, home exercise was an alternative for those who could not or did not want to go to a gymnasium. The gym industry invented methods and apparatus to make physical exercise at home easier. This paper aims to describe these kinds of home gymnasiums and stimulate circumstantial and original narrative. Through the press and historical bibliographical sources of the time, we reviewed the subject in publications up to 1912. Finally, this narrative serves to conclude a problematization in the environment of Spain’s weak physical culture at the beginning of the twentieth century.